Climate policy uncertainty and bank systemic risk: A creative destruction perspective - Liu, Yulin; Wang, Junbo; Wen, Fenghua; Wu, Chunchi (Journal of Financial Stability, 2024)
We conduct an international study on the effect of climate policy uncertainty on the systemic risk of banks from G20 countries. We find that climate policy uncertainty is associated with lower bank systemic risk. This relation is more pronounced in countries with high innovation capacity, climate readiness, more systemically important banks, and a more competitive banking system. Climate-related information disclosure and sustainable investments are critical economic channels through which the effect of climate policy uncertainty works. Our findings alleviate the concern that climate transition risk may contribute to financial instability and provide practical implications for regulators to design climate transition policies.